2012
DOI: 10.1161/circulationaha.112.090977
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Cardiac Hypertrophy Alters Intracellular Targeting of Phosphodiesterase Type 5 From Nitric Oxide Synthase-3 to Natriuretic Peptide Signaling

Abstract: Background In the normal heart, phosphodiesterase type 5 (PDE5) hydrolyzes cGMP coupled to nitric oxide (specifically from NOS3) but not natriuretic peptide (NP) stimulated guanylyl cyclase. PDE5 is upregulated in hypertrophied and failing hearts and is thought to contribute to their pathophysiology. Since NO signaling declines whereas NP-derived cGMP rises in such diseases, we hypothesized that PDE5 substrate selectivity is retargeted to blunt NP-derived signaling. Methods and Results Mice with cardiac myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…This is even more critical when examining phosphodiesterases, which control highly compartmentalized cAMP pools, and redistribution phenomena under pathological conditions have been reported. 52,53 Despite designing our experiments after general recommendations for state-of-the-art phenotyping of transgenic mice, 36 we are not able to fully exclude artificial compartmentation effects. However, the specificity of the phenotype and its striking similarities to in vivo studies of endogenous phosphodiesterase 2 from mice and larger animals offers a valid approach for analyzing the pathophysiological role of phosphodiesterase 2 in heart function.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…This is even more critical when examining phosphodiesterases, which control highly compartmentalized cAMP pools, and redistribution phenomena under pathological conditions have been reported. 52,53 Despite designing our experiments after general recommendations for state-of-the-art phenotyping of transgenic mice, 36 we are not able to fully exclude artificial compartmentation effects. However, the specificity of the phenotype and its striking similarities to in vivo studies of endogenous phosphodiesterase 2 from mice and larger animals offers a valid approach for analyzing the pathophysiological role of phosphodiesterase 2 in heart function.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…Recent advances have revealed that many signaling components in the network form compartments and/or multi-protein signaling complexes (“signalosomes”) [1, 2, 25, 104107]. With advancements in methods for spatiotemporally-resolved recording of cAMP [1, 2, 25, 104107] and cGMP [49, 108, 109], extending the model to include these additional mechanisms is an important next step to understand diversification of cN signals in subcellular micro-domains and communication between these cellular compartments. Under conditions exhibiting high [cGMP], cAMP-cGMP positive cross-talk is likely to be more substantial than that shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3). The PDE isoforms and their splice variants have subcellular regional specificity; PDE2A is confined to the membrane with the sarcomeric Z-band [36], PDE3A isoforms are either cytosolic or membrane-associated [37], and PDE5 localizes to the cardiomyocyte sarcomeric Z-band but becomes diffusely distributed in pathologically hypertrophied hearts [38,39]. Local cGMP pools within cardiomyocytes likely change over time with chronic volume-overload, as the relative expression and subcellular localization of these cardiac PDE isoforms vary along with the relocalization of the sGC subunits, and may mark the transition from compensated eccentric hypertrophy to clinical decompensation.…”
Section: Discussionmentioning
confidence: 99%